The Savings Illusion — Why Clinical Quality Improvement Fails to Deliver Bottom-Line Results - Rauh, Stephen S; Wadsworth, Eric B; Weeks, Bill; Weinstein, James (The New England Journal of Medicine, 2011)
Many people believe that improving clinical quality — reducing readmissions, shortening lengths of stay, and building efficiency into clinical processes — will reduce health care costs. So why haven't years of work in quality improvement had a measurable effect on costs?